Acute nerve stretch and the compound motor action potential - Stecker, Mark M; Baylor, Kelly; Wolfe, Jacob; Stevenson, Matthew (Journal of Brachial Plexus and Peripheral Nerve Injury, 2011)
In this paper, the acute changes in the compound motor action potential (CMAP) during mechanical stretch were studied in hamster sciatic nerve and compared to the changes that occur during compression.In response to stretch, the nerve physically broke when a mean force of 331 gm (3.3 N) was applied while the CMAP disappeared at an average stretch force of 73 gm (0.73 N). There were 5 primary measures of the CMAP used to describe the changes during the experiment: the normalized peak to peak amplitude, the normalized area under the curve (AUC), the normalized duration, the normalized velocity and the normalized velocity corrected for the additional path length the impulses travel when the nerve is stretched. Each of these measures was shown to contain information not available in the others.During stretch, the earliest change is a reduction in conduction velocity followed at higher stretch forces by declines in the amplitude of the CMAP. This is associated with the appearance of spontaneous EMG activity. With stretch forces < 40 gm (0.40 N), there is evidence of increased excitability since the corrected velocities increase above baseline values. In addition, there is a remarkable increase in the peak to peak amplitude of the CMAP after recovery from stretch < 40 gm, often to 20% above baseline.Multiple means of predicting when a change in the CMAP suggests a significant stretch are discussed and it is clear that a multifactorial approach using both velocity and amplitude parameters is important. In the case of pure compression, it is only the amplitude of the CMAP that is critical in predicting which changes in the CMAP are associated with significant compression.